2013
DOI: 10.1175/jcli-d-12-00774.1
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Modes of Wintertime Upper-Tropospheric Temperature Variations over Asia and Links to Surface Climate

Abstract: In this study, the authors investigate the variations and predictability of wintertime upper-tropospheric temperature (UTT) over Asia, which are often linked to severe climate anomalies, and the associated features of large-scale circulation and surface climate. The ECMWF Interim Re-Analysis (ERA-Interim) and hindcast of the NCEP Climate Forecast System, version 2 (CFSv2), are mainly analyzed.The first empirical orthogonal function mode of UTT shows a dipole structure, with a strong positive center over southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…4c). These features are overall similar with those in observations shown in many previous studies (e.g., Yang et al 2008;Jiang et al 2013b).…”
Section: ) Impact Of Entire Tp Heatingsupporting
confidence: 91%
See 2 more Smart Citations
“…4c). These features are overall similar with those in observations shown in many previous studies (e.g., Yang et al 2008;Jiang et al 2013b).…”
Section: ) Impact Of Entire Tp Heatingsupporting
confidence: 91%
“…Previous studies (Liu and Yanai 2001;Nan et al 2009;Zhao et al 2010Zhao et al , 2011Zhao et al , 2012Zuo et al 2012Zuo et al , 2013Jiang et al 2013a) have shown a highly positive relationship between surface temperature and tropospheric temperature, here the vertically integrated temperature from 500 hPa (700 hPa if topography is below 3000 m) to 200 hPa, owing to the hydrostatic characteristics of the atmosphere. Increases in tropospheric temperature can be induced by the increase in regional heat transfer from the surface to the atmosphere (Zhao et al 2012).…”
Section: A Major Features Of Tp Impact On Regional Monsoonsmentioning
confidence: 83%
See 1 more Smart Citation
“…The multiscale mountain ranges have significant impacts on atmospheric circulation, energy, and water cycles of the climate system by dynamics and thermodynamic effects (e.g., Boos & Kuang, ; Boos & Kuang, ; Yanai et al, ; Wu & Zhang, ; Wu & Liu, ; Wu, Liu et al, ). Earlier theoretical and numerical modeling studies have mainly focused on the mechanical forcing (Bolin, ; Charney & Eliassen, ; Yeh, ), while more and more attention has been paid to the thermal forcing of TP during recent decades (Yanai et al, ; Wu & Zhang, ; Duan & Wu, ; Wu et al, , 2012; Jiang et al, , , ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While Shaman and Tziperman () proposed that ENSO affects the snow depth over the TP by exciting a stationary Rossby wave extending along the North African‐Asian jet, many previous studies have reported that ENSO could affect East Asian climate by modulating convection over the western Pacific (Chang et al, ; Lau & Nath, ; Wang et al, ). Jiang et al () found that interannual variability of wintertime surface air temperature over the southeastern TP is linked to convection anomaly over the western North Pacific (WNP), which is significantly affected by ENSO. As surface air temperature can affect snow depth/snow cover (Bao & You, ; Bojariu & Gimeno, ; Wang et al, ), is it possible that ENSO can affect snow depth/snow cover over the TP by modulating the convection over the WNP?…”
Section: Introductionmentioning
confidence: 99%